2016
DOI: 10.1186/s12993-016-0105-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of epilepsy on autistic symptom severity assessed by the social responsiveness scale in children with autism spectrum disorder

Abstract: Background: As the prevalence of autism spectrum disorders in people with epilepsy ranges from 15 to 47 % (Clarke et al. in Epilepsia 46:1970-1977, it is speculated that there is a special relationship between the two disorders, yet there has been a lack of systematic studies comparing the behavioral phenotype between autistic individuals and autistic individuals with epilepsy. This study aims to investigate how the co-occurrence of epilepsy and Autism Spectrum Disorder (ASD) affects autistic characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 38 publications
(69 reference statements)
1
26
0
1
Order By: Relevance
“…Conditional regression analyses showed that neurological problems were associated with the severity of autistic traits in our whole sample. This is in line with the results of prior research, where individuals with neurological conditions displayed more challenges with social communication and facial emotion recognition compared to those without, independent of intellectual disability (Ko et al 2016;Richard et al 2017). Our results support the hypothesis that common neurological alterations impact on social brain networks to generate autistic phenotypes (Richard et al 2017).…”
Section: Discussionsupporting
confidence: 93%
“…Conditional regression analyses showed that neurological problems were associated with the severity of autistic traits in our whole sample. This is in line with the results of prior research, where individuals with neurological conditions displayed more challenges with social communication and facial emotion recognition compared to those without, independent of intellectual disability (Ko et al 2016;Richard et al 2017). Our results support the hypothesis that common neurological alterations impact on social brain networks to generate autistic phenotypes (Richard et al 2017).…”
Section: Discussionsupporting
confidence: 93%
“…These clinical features may be caused by a variety of genetic abnormalities and environmental factors and may also temporarily overlap with other disorders including Rett syndrome (Park et al., 2016). ASD may be also associated with epilepsy (15%–47% of cases) and intellectual disability (8%–39% of cases; Ko, Kim, Kim, Song, & Cheon, 2016; La Malfa, Lassi, Bertelli, Salvini, & Placidi, 2004). …”
Section: Introductionmentioning
confidence: 99%
“…In juvenile-age macaques, peer-related activities -such as aggression -continue to be present at high rates until puberty (46), which suggests that animals exhibiting lower amounts of aggressive behavior might be more immature or have poorer social skills. Impaired motor coordination, postural control and balance has been reported in children with ASD (41-43), as well as staring off into space (47,48).…”
Section: Discussionmentioning
confidence: 99%